Catenin α 1 mutations cause familial exudative vitreoretinopathy by overactivating Norrin/β-catenin signaling - Zhu, Xianjun; Yang, Mu; Zhao, Peiquan; Li, Shujin; Zhang, Lin; Huang, Lulin; Huang, Yi; Fei, Ping; Yang, Yeming; Zhang, Shanshan; Xu, Huijuan; Yuan, Ye; et al. (The Journal of Clinical Investigation, 2021)
Familial exudative vitreoretinopathy (FEVR) is a severe retinal vascular disease that causes blindness. FEVR has been linked to mutations in several genes associated with inactivation of the Norrin/β-catenin signaling pathway, but these account for only approximately 50% of cases. We report that mutations in α-catenin (CTNNA1) cause FEVR by overactivating the β-catenin pathway and disrupting cell adherens junctions. We identified 3 heterozygous mutations in CTNNA1 (p.F72S, p.R376Cfs*27, and p.P893L) by exome sequencing and further demonstrated that FEVR-associated mutations led to overactivation of Norrin/β-catenin signaling as a result of impaired protein interactions within the cadherin-catenin complex. The clinical features of FEVR were reproduced in mice lacking Ctnna1 in vascular endothelial cells (ECs) or with overactivated β-catenin signaling by an EC-specific gain-of-function allele of Ctnnb1. In isolated mouse lung ECs, both CTNNA1-P893L and F72S mutants failed to rescue either the disrupted F-actin arrangement or the VE-cadherin and CTNNB1 distribution. Moreover, we discovered that compound heterozygous Ctnna1 F72S and a deletion allele could cause a similar phenotype. Furthermore, in a FEVR family, we identified a mutation of LRP5, which activates Norrin/β-catenin signaling, and the corresponding knockin mice exhibited a partial FEVR-like phenotype. Our study demonstrates that the precise regulation of β-catenin activation is critical for retinal vascular development and provides new insights into the pathogenesis of FEVR.